(untitled) (Journal of Hama University, 2024)
This field experiment was carried out in Qutaylibiyah in Jableh countryside the during the agricultural season 2023-2024, to study the effect of plant density on the growth of the common Mallow plant, Malva sylvestris L. The seeds were planted on 1/11/2023. The experiment included four planting densities of 45 x 10 cm, 45 x 20 cm, 45 x 30 cm, 45 x 40 cm. The experiment was designed according to a completely randomized block design with three replicates for each treatment. The results showed a significant effect of plant density on all studied traits. High density achieved the highest plant height (70.35 cm), while low density achieved the highest number of branches (8.05 branches/plant), the highest number of leaves on the plant (40.20 leaves), and the highest area. Leaf size (70.25 cm2), highest root length (27.25 cm), and highest root diameter (1.51 cm).